The Processes of Lipoperoxidation and Antioxidant Protection in Men with Different Variants of Spermograms - N. A. Kurashova; B. G. Dashiev; M. I. Dolgikh; L.I. Kolesnikovа (International Journal of Biomedicine, 2019)
Background: Currently, infertile couples represent a very complex and serious medical and social problem. In 40%-60% of cases, the reason for the absence of children in the family is the male factor. Oxidative stress (OS) has been identified as one of the many mediators of male infertility by causing sperm dysfunction. The purpose of this study was to identify the characteristics of the intensity indices of lipid peroxidation (LPO) and antioxidant system (AOS) in the ejaculate of men with different spermogram variants. Materials and Methods: We performed a retrospective analysis of the results of examinations of 69 men of infertile couples with various disorders of the ejaculate and 155 healthy men with proven fertility. In the semen of the examined men, the level of CD (conjugated dienes), TBARS (thiobarbituric acid reactive substances), α-tocopherol, retinol and total antioxidant activity (AOA) was evaluated by spectrophotometric method. Results: We found that the antioxidant protection system in patients with asthenozoospermia was characterized by a decrease in the level of total AOA in the semen by 50% and the α–tocopherol concentration by 52%, compared to healthy men in the control group. In patients with oligozoospermia, an increase in the CD concentration by 39% and a decrease in the TBARS concentration by 26% was found; the level of total AOA decreased by 37% and the concentration of α–tocopherol by 41%, compared to healthy men. Conclusion: In general, the analysis of the obtained data of the survey of men with different variants of spermograms indicates a change in the parameters of the LPO–AOS and confirms the OS development. Thus, it can be noted that depending on the pathological state of the ejaculate in men of reproductive age, LPO processes have their own characteristics, and in men with oligozoospermia, LPO processes occur more intensively. Activation of LPO-AOS processes can be both a consequence and a cause of various metabolic changes in the human body.